Glucose-6-phosphate dehydrogenase deficiency and long-term risk of immune-related disorders - Israel, Ariel; Schäffer, Alejandro A.; Berkovitch, Matitiahu; Ozeri, David J.; Merzon, Eugene; Green, Ilan; Golan-Cohen, Avivit; Ruppin, Eytan; Vinker, Shlomo; Magen, Eli (Frontiers in Immunology, 2023)
Introduction Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an X-linked enzymatic disorder that is particularly prevalent in Africa, Asia, and the Middle East. This study aimed to assess the long-term health risks associated with G6PD deficiency. Methods A retrospective cohort study was conducted using data from a national healthcare provider in Israel (Leumit Health Services). A total of 7,473 G6PD-deficient individuals were matched with 29,892 control subjects in a 1:4 ratio, based on age, gender, socioeconomic status, and ethnic groups. The exposure of interest was recorded G6PD diagnosis or positive G6PD diagnostic test. The main outcomes and measures included rates of infectious diseases, allergic conditions, and autoimmune disorders between 2002 and 2022. Results Significantly increased rates were observed for autoimmune disorders, infectious diseases, and allergic conditions in G6PD-deficient individuals compared to the control group. Specifically, notable increases were observed for rheumatoid arthritis (odds ratio [OR] 2.41, p<0.001), systemic lupus erythematosus (OR 4.56, p<0.001), scleroderma (OR 6.87, p<0.001), pernicious anemia (OR 18.70, p<0.001), fibromyalgia (OR 1.98, p<0.001), Graves’ disease (OR 1.46, p=0.001), and Hashimoto’s thyroiditis (OR 1.26, p=0.001). These findings were supported by elevated rates of positive autoimmune serology and higher utilization of medications commonly used to treat autoimmune conditions in the G6PD-deficient group. Discussion In conclusion, individuals with G6PD deficiency are at a higher risk of developing autoimmune disorders, infectious diseases, and allergic conditions. This large-scale observational study provides valuable insights into the comprehensive association between G6PD deficiency and infectious and immune-related diseases. The findings emphasize the importance of considering G6PD deficiency as a potential risk factor in clinical practice and further research is warranted to better understand the underlying mechanisms of these associations.